Back on track! : successful management techniques to get a company out of debt pile - Bieck, Olga (Anchor Academic Publishing, 2014)
The present work is analysing the successful turnaround of the Japanese car manufacturer Nissan in 1999 to 2001. Very often transformational change fails due to different factors, in most cases though due to the insufficient employee's motivation or due to cultural problems when two international partners try to gain the competitive advantage through merger or alliance. To analyse the successful turnaround of Nissan after its alliance with Renault, a 'new' model for conducting organizational change was introduced. The provided framework unites both actions and attitudes, necessary for motivati.